RaspyAir: self-monitoring system for wireless intrusion detection using raspberry pi / Mohd Nizam Osman and Mohd Syafiq Aiman Mohamad Zulrahim - Osman, Mohd Nizam; Mohammad Zulrahim, Mohd Syafiq Aiman (UiTM Cawangan Perlis, 2016)
This paper described a self-monitoring for wireless intrusion-detection system (IDS) using Raspberry Pi to enhance the security performance for personal computers. Nowadays, most of the personal computers are interconnected without wire. Therefore, everybody can easily connect to the Internet and indirectly exposed to the security issues, especially the safety of the confidential data. Sometimes, we do not know that someone is sniffing our network, even we do not realize that there was an intruder in our network due to most of the personal computers does not have the intruder monitoring system. To overcome this problem, we proposed a system for wireless monitoring and intruder detection for personal computer known as RaspyAir. This system was implemented using misuse detection approach, which is hybridization of tShark and Airodump-ng to capture the possibility of the traffic in the wireless environment. The brute-force algorithm is used to filter the traffic using signature based detection technique. Then, RaspyAir was integrated with a credit card size single board computer, which is Raspberry Pi as an external tool for monitoring system. The developed system is then tested using code auditing and penetration testing to identify the achievement of the system. After applying the testing from Wireless Security Assessment Methodology (WSAM), a standard measure score is calculated to evaluate the degree of the security for the system. Hence, the result has shown the RaspyAir followed the security guidelines, fully secured, can be deployed for personal computer and significantly increase the security performance for monitoring wireless intrusion-detection system. Additionally, from the experiment conducted has confirmed that by using Raspberry Pi as an external tool, it consumed nine times less electrical power compared to the personal computer.